IDEOLOGICAL DETERMINANTS OF POLITICAL SCIENCE IN UKRAINE - Власенко, Т.Т. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This article considers the problem of ideological conditioning of political science in the national scientific discourse. The author analyzes the search algorithm using the methodological approaches of the scientific analysis of Ukrainian realities, in particular, the strategy of development of the Ukrainian state.Today, the task of political science is to develop a research methodology transformation processes in the Ukrainian society.